Diagnostic imaging in musculoskeletal trauma - general principles - Rodrigues, Marcelo Bordalo (Revista de Medicina, 2011)
Imaging methods are essential in the diagnosis of a bone fracture. Imaging evaluation starts with a simple x-ray, providing essential information regarding bony structures. Other imaging methods have a secondary role, complementary to the radiographs, especially MRI and CT. These methods may be used in cases of a normal x-ray with positive clinical examination or when a detailed presurgical evaluation is necessary